Assessment of anti-inflammatory activity of Tridax procumbens in wistar rats - Sandeep Prakash; Rajesh Kumar Suman; Gulab Chandra; Priti Yadav; Manish Kumar (MGM Journal of Medical Sciences, 2022)
Background: Tridax procumbens Linn. is a spreading herb found throughout India. Tridax procumbens is known for several potential therapeutic effects like antiviral, antioxidant, anti-infective, wound healing, insecticidal and anti-inflammatory, hepatoprotective, and antidiabetic. Novel therapies for inflammation are essential to overcome the adverse effects of existing anti-inflammatory drugs. Thus, this study was designed to evaluate anti-inflammatory activity in the experimental animal. Objective: To evaluate anti-inflammatory efficacy in experimental animalMaterials and Methods: Tridax procumbens plant leaves were taken for the study. The Plant extraction was prepared by using the Soxhlet apparatus. The ethanolic extract was used as a test drug. Indomethacin and Dexamethasone were used as control drugs. Wistar rats weighing 150g to -200g were used in the study. Results: At dosages of 200 and 400 mg kg-1, the ethanolic leaf extracts of Tridax Procumbens demonstrated substantial anti-inflammatory activity against Irish Moss-triggered inflammation. After 3 hours, 400 mgkg-1 showed a significant reduction in inflammation (48 percent), with the impact increasing after 3 hours (52 percent). The anti-inflammatory efficacy of Tridax Procumbens ethanol (EtOH) extracts was substantial and comparable to that of indomethacin (10 mg/kg). Tridax procumbens ‘s Ethanol (EtOH) leaf extract at a dose of 200 and 400 mgkg-1, demonstrated considerable anti-inflammatory action. The average weight of granulomatous surrounding tissue in the threading was considerably smaller in the Tridax procumbens extraction group after 7 days than in the comparison group. The 400 mg kg-1 dose was shown to be the most effective of the two. the greatest reduction in the production of granuloma tissue. Tridax procumbens at doses of 200 mg/kg and 400 mg/kg resulted in substantial reductions in granuloma weights of 38.16 ± 0.04 (7.4 percent inhibition) and 34.58 ± 0.04 (16.1 percent inhibition), respectively. The lower dose of 400 mg/kg resulted in a little lesser reduction in granumola weight than the conventional medication dexamethasone (28.92 ± 0.04). (29.8 percent inhibition). Conclusion: The present study concludes that Tridax Procumbens possess anti-inflammatory effects in animal models.